Hybrid Additives-Subtractive Manufacturing of Multi-Layer PCBs Using Laser Direct Structuring (LDS) and Inkjet printing - Goti, Ankit Bharatbhai (International Journal of Scientific Research and Management (IJSRM), 2025)
The increasing demand for miniaturized, high-performance, and lightweight electronic systems—particularly in applications such as wearable technology, automotive sensors, and medical implants—has driven a paradigm shift in printed circuit board (PCB) manufacturing. Traditional subtractive manufacturing methods, though reliable, pose limitations in terms of design flexibility, environmental sustainability, and scalability for complex three-dimensional structures. In response to these challenges, hybrid manufacturing processes that combine additive and subtractive techniques have emerged as a transformative solution.This article explores a novel hybrid approach integrating Laser Direct Structuring (LDS) with Inkjet Printing to fabricate multi-layer PCBs with enhanced structural and electrical performance. LDS enables high-resolution patterning on 3D substrates by selectively activating surfaces for electroless metal deposition, offering precise subtractive control. Complementarily, inkjet printing introduces additive capabilities, enabling the selective deposition of functional inks for fine features, layer stacking, and cost-effective customization.The study presents a comprehensive analysis of the process flow, materials compatibility, and parameter optimization needed to harmonize these two technologies. Furthermore, we discuss the implications for high-density interconnects (HDIs), thermal management, and circuit complexity in multi-layer architectures. The hybrid LDS–inkjet platform demonstrates not only the potential to improve design agility and production efficiency but also marks a significant step toward more sustainable and digitally-driven electronics manufacturing. Future outlooks suggest integration with AI-based design automation and nanomaterial-enhanced inks to further extend the capabilities of this hybrid paradigm.